2003 Handbook of Employment Regulations Affecting Florida Farm Employers and Workers: Worker Protection Standard -- EPA [Federal] - Leo C. Polopolus; Michael T. Olexa; Fritz Roka; Carol Fountain (EDIS, 2003)
The purpose of the EPA Worker Protection Standard is to provide federal safety standards for users, employers, workers, and handlers of agricultural pesticides. This is EDIS document FE422, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published July 2003. This information is included in Circular 1200, Handbook of Employment Regulations Affecting Florida Farm Employers and Workers.